The prevalence of posture pathology in school-aged children (results of a population-based study with the use of the computerized photo-geometric program “Posture”) - I. O. Afanasieva; M. V. Khaitovych; V. S. Potaskalova; I. V. Andrushchenko; V. V. Yevminov; I. O. Kudelia (Zaporožskij Medicinskij Žurnal)
Pathology of posture in children remains currently unresolved problem. According to foreign studies in the general population, the occurrence of idiopathic scoliosis in adolescents with an angle above 10º according to Cobb accounts for 0.93 % to 12.00 %. In Ukraine, the prevalence of posture pathology is not known.